Study on caesarean section rate using Robsons ten group classification system and its implications- a retrospective analysis from a medical college in the union territory of Puducherry - K., Sukanya; Jaget, Nirmala; Sekar, Sindhujha; P. B., Hiremath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Caesarean section is one of the major surgeries in obstetrics and it helps in preventing various complications and difficult labour ensuring the safety of both mother and baby. The aim of the study was to analyse the rate and various indication of caesarean section in our hospital and to analyse it using RTGCS. Methods: Retrospective data collected from hospital records in the department of obstetrics and gynecology of SVMCH, Puducherry from January 2021 till January 2024 have been taken and analysed to study the various indications of caesarean section and to classify them according to RTGCS. Results: Out of 2022 deliveries conducted during the study period, 984 (48.6%) were caesarean section. The most common indication of CS was previous LSCS (35.6%), belongs to group- 5 of RTGCS followed by fetal distress (20.5%). Other common indications were failed induction (7.4%), breech (4.3), IVF/twin (5.8%). 6% of women underwent preterm CS (group 10 of RTGCS). Around 1% of the women underwent CS for malposition/malpresentation and maternal request. Conclusions: In our study, the rate of caesarean section is higher compared to WHO recommendation. Caesarean section if performed when needed utmost in case of obstetrics risks and emergencies may reduce the rate of CS. Trial of labour can be considered for women with previous CS who were the major contribution for repeat CS. Proper counselling and education to the mother may help in reducing the fear and anxiety about normal vaginal delivery, thus reduces the rate of other non-obstetrics indication like maternal request.